Disease-associated genotypes of the commensal skin bacterium Staphylococcus epidermidis. Issue 1 (December 2018) - Méric, Guillaume; Mageiros, Leonardos; Pensar, Johan; Laabei, Maisem; Yahara, Koji; Pascoe, Ben; Kittiwan, Nattinee; Tadee, Phacharaporn; Post, Virginia; Lamble, Sarah; Bowden, Rory; Bray, James; et al.
Abstract Some of the most common infectious diseases are caused by bacteria that naturally colonise humans asymptomatically. Combating these opportunistic pathogens requires an understanding of the traits that differentiate infecting strains from harmless relatives.Staphylococcus epidermidis is carried asymptomatically on the skin and mucous membranes of virtually all humans but is a major cause of nosocomial infection associated with invasive procedures. Here we address the underlying evolutionary mechanisms of opportunistic pathogenicity by combining pangenome-wide association studies and laboratory microbiology to compareS. epidermidis from bloodstream and wound infections and asymptomatic carriage. We identify 61 genes containing infection-associated genetic elements (k-mers) that correlate with in vitro variation in known pathogenicity traits (biofilm formation, cell toxicity, interleukin-8 production, methicillin resistance). Horizontal gene transfer spreads these elements, allowing divergent clones to cause infection. Finally, Random Forest model prediction of disease status (carriage vs. infection) identifies pathogenicity elements in 415 S. epidermidis isolates with 80% accuracy, demonstrating the potential for identifying risk genotypes pre-operatively. Staphylococcus epidermidis is carried asymptomatically by virtually all humans but is also a major cause of nosocomial infection. Here, the authors study 141 isolates from healthy carriage and 274 isolates from clinical infections, and identify genes and genetic elements associated with pathogenicity.